Numerical Aeroacoustic Assessment of a Metacontinuum Device Impinged by a Laser-Generated Sound Source - Giada Colombo; Giorgio Palma; Umberto Iemma (Journal of Engineering)
Significant research efforts have been conducted by many research groups in the last decades to circumvent the acoustic metamaterial concept limitations. Principally, the lack of a reliable methodology for the design of such metamaterial-based devices and their performance decay when they operate in a moving medium were the main topics of investigation that culminated in a number of possible approaches with a high potential of application in aeroacoustics. One of these approaches is based on the aeroacoustic spacetime reformulation of the problem to recast the governing equations in a generalized form, independent of the kinematic conditions of the supporting medium. In the present paper, the response of a spacetime-corrected metacontinuum is coupled with a high-fidelity aeroacoustic model of the hosting fluid to allow for the modelling of actual experimental realizations of a laser-generated sound source. The availability of a reliable model to couple the convective metacontinuum design with the heat-release source would make possible the systematic cross-validation of the numerical simulations with the experimental results obtained in the most advanced testing facilities, paving the way to an effective inclusion of metacontinuum-based devices in aeronautics and, finally, in a simulation-based, multidisciplinary design optimization framework. Although the method presented is valid for arbitrary acoustic responses, the numerical simulations presented in this work have been conducted using the classic Cummer–Schurig inertial cloaking as a reference application, which can now be considered a widely accepted benchmark for acoustic metamaterial applications.